2022
DOI: 10.3390/antiox11061193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Magnetite Nanoparticles Coated with Aspartic Acid on the Growth, Antioxidant Enzymes Activity and Chlorophyll Content of Maize

Abstract: In recent decades, magnetite nanoparticles received greater attention in nanobiotechnology due to wide applications. This study presents the influence of the oxidative stress caused by magnetite nanoparticles coated with aspartic acid (A-MNP) of 9.17 nm mean diameter size, on maize (Zea mays) seedlings, in terms of growth, enzymatic activity and chlorophyll content as evaluated in exposed plant tissues. Diluted suspensions of colloidal magnetite nanoparticles stabilized in water were added to the culture mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Contrarily, the exposure of fish to MNG in the Pb-exposed group has an antioxidant-protecting effect indicated by a clear modulation in the antioxidant biomarkers (elevated SOD and CAT activities) resulting in protection from oxidative damage. In line with a recent finding, Răcuciu et al [ 45 ] confirmed that Fe 3 O 4 NPs have potent antioxidant enzymatic activity via modulating the levels of CAT and SOD and aid in plant development. Moreover, Fe 3 O 4 NPs can enhance the antioxidant status and reduce the oxidative stress of O. niloticus and Indian major carp ( Labeo rohita ) [ 14 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 85%
“…Contrarily, the exposure of fish to MNG in the Pb-exposed group has an antioxidant-protecting effect indicated by a clear modulation in the antioxidant biomarkers (elevated SOD and CAT activities) resulting in protection from oxidative damage. In line with a recent finding, Răcuciu et al [ 45 ] confirmed that Fe 3 O 4 NPs have potent antioxidant enzymatic activity via modulating the levels of CAT and SOD and aid in plant development. Moreover, Fe 3 O 4 NPs can enhance the antioxidant status and reduce the oxidative stress of O. niloticus and Indian major carp ( Labeo rohita ) [ 14 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, the positive control treated with vitamin C also significantly induced the antioxidant enzymes, catalyzing the conversion of superoxides (O 2 − ) to less reactive H 2 O 2 [ 7 ]. The loss of SOD activity is linked to membrane lipid peroxidation, protein carbonylation, and DNA breakage [ 8 ]. Lipid peroxidation (POD) is a well-known mechanism, used as an indicator of oxidative stress in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mangifera indica L. is a popular fruit whose extract has been reported to have several beneficial medicinal properties other than nutritional purposes [ 4 ]. Its peels and kernel extracts comprising 40–50% of its weight contain a high amount of bioactive compounds i.e., gallic acids, quercetin, mangiferin, catechin, epicatechin, quercetin, isoquercetin, fisetin, rutin, ellagic acid, gallic acid, gallates, condensed tannins, gallotannins, anthocyanin, and astragalin [ 5 , 6 , 7 , 8 , 9 ]. These compounds have good potency to control the overproduction of FRs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of antioxidant potential will provide an insight regarding the interactions of target compound with biomolecules inside the living cell. Thus, it is useful to study the role of metal oxide nanoparticles as antioxidants because of their current applications and uses in biological systems [ [109] , [110] , [111] ].It has been observed that the antioxidant potential of biofabricated nanoparticles relies on the redox potential of flavonoid and phenolic compounds present on their surface [ 112 , 113 ].
Fig.
…”
Section: Antioxidant Activities Of Mycogenic Metallic Nanoparticlesmentioning
confidence: 99%